SIKAP POLITIK SANTRI PONDOK PESANTREN PADA PERKEMBANGAN ISU POLARISASI POLITIK DI KABUPATEN CIAMIS - Yudi Rusfiana; Agus Nurulsyam; Nindya Adhisty (Jurnal Academia Praja, 2026)
The issue of political polarization in Indonesia is not new. Differences in views between groups always arise when facing political events at both the national and local levels. Ciamis Regency, located east of West Java, directly borders Central Java Province. Its strategic geographic location and relatively high population growth make the existence of Islamic boarding schools (pesantren) an alternative for the community to meet their educational needs. The method and approach used were descriptive qualitative, with informants consisting of several students from Islamic boarding schools in Ciamis Regency and several alumni figures encountered incidentally. The results of this study indicate that the political attitudes of Islamic boarding school students, particularly those at Islamic boarding schools in Ciamis Regency, toward polarization, particularly in national and local political developments such as the presidential and regional elections, tend to be flat, meaning they follow developments, even if affiliation with a group is relatively homogeneous. Therefore, understanding the development of political dynamics among Islamic boarding school students is still needed to increase their political participation.